2014
DOI: 10.1146/annurev-chembioeng-060713-035958
|View full text |Cite
|
Sign up to set email alerts
|

A New Toolbox for Assessing Single Cells

Abstract: Unprecedented access to the biology of single cells is now feasible, enabled by recent technological advancements that allow us to manipulate and measure sparse samples and achieve a new level of resolution in space and time. This review focuses on advances in tools to study single cells for specific areas of biology. We examine both mature and nascent techniques to study single cells at the genomics, transcriptomics, and proteomics level. In addition, we provide an overview of tools that are well suited for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 135 publications
(179 reference statements)
0
28
0
Order By: Relevance
“…ChIP-seq, RNA-seq, MS-based proteomics) in a multi-and cross-species manner. Finally, a current challenge in biology resides in the development of methods to investigate single cells at the genomic, transcriptomic, proteomic, and metabolomic level (for review, see Tsioris et al (2014)). The use of these so-called single-cell approaches will mandate the more detailed study of the kinetics of germ cell differentiation and, most importantly, enable us to gain insight into the biology of discrete cell populations within the testis, such as the spermatogonial stem cell.…”
Section: Resultsmentioning
confidence: 99%
“…ChIP-seq, RNA-seq, MS-based proteomics) in a multi-and cross-species manner. Finally, a current challenge in biology resides in the development of methods to investigate single cells at the genomic, transcriptomic, proteomic, and metabolomic level (for review, see Tsioris et al (2014)). The use of these so-called single-cell approaches will mandate the more detailed study of the kinetics of germ cell differentiation and, most importantly, enable us to gain insight into the biology of discrete cell populations within the testis, such as the spermatogonial stem cell.…”
Section: Resultsmentioning
confidence: 99%
“…Single cells have been studied since the invention of the microscope, but it is not until recently that genome-scale approaches have been applied to single-cell biology [37] (Box 1). For example, microfluidic-based single-cell sorting methods [8,9], high-throughput multiplexed quantitative PCR (qPCR) [1014] or sequencing approaches [1523], mass cytometry-based proteomic strategies [2426], and data analysis methods [2730] provided an unprecedented opportunity to identify rare cell types, such as cancer stem cells, and to investigate the dynamic processes of cell-fate transitions.…”
Section: Cancer Is a Disease Of Multitudesmentioning
confidence: 99%
“…With respect to current mixtures found in the field of analytical chemistry, living cells exhibit several features making them highly singular: 1) Transcriptomics, proteomics, and metabolomics approaches—sometimes carried out down to the single cell level—have shown that cells contain an extremely large number of components (typically more than 10 6 ), which essentially share similar elemental composition and functional groups; 2) The molar concentrations of the cell components cover an extremely large dynamic range, from 10 −1 mol L −1 for ions such as Na + , K + , or Cl − , to 10 −12 mol L −1 for DNA; 3) Cells exhibit a multi‐scale spatial heterogeneity and a multi‐scale dynamics at steady‐state . Their components are heterogeneously but precisely distributed in multiple compartments.…”
Section: Living Cells Are Singular Chemical Mixtures To Analyzementioning
confidence: 99%